2015
DOI: 10.3390/electronics4030651
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Materials for Sensing: Graphene and Beyond

Abstract: Two-dimensional materials have attracted great scientific attention due to their unusual and fascinating properties for use in electronics, spintronics, photovoltaics, medicine, composites, etc. Graphene, transition metal dichalcogenides such as MoS2, phosphorene, etc., which belong to the family of two-dimensional materials, have shown great promise for gas sensing applications due to their high surface-to-volume ratio, low noise and sensitivity of electronic properties to the changes in the surroundings. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
174
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(175 citation statements)
references
References 181 publications
(272 reference statements)
1
174
0
Order By: Relevance
“…This Special Issue comprises a total of 12 papers (four review papers and eight contributed articles) and spans a wide range of topics, which extend from first principle band structure calculations [14] and molecular dynamics simulations of the thermal properties [15] of 2D materials, over numerical simulations and compact modeling of 2D transistors [16][17][18] and other 2D devices [19,20], 2D material growth [21,22] and processing issues [22][23][24], up to experimental 2D devices and their applications [22,23,25]. Regarding the materials, the papers of the Special Issue deal with graphene and graphene nanoribbons [16][17][18][19][20]22,23,25], TMDs (transition metal dichalcogenide) [14,21,22,24,25], phosphorene, which frequently is called 2D black phosphorus [24,25], and 2D metal oxides [25].…”
Section: The Present Special Issuementioning
confidence: 99%
“…This Special Issue comprises a total of 12 papers (four review papers and eight contributed articles) and spans a wide range of topics, which extend from first principle band structure calculations [14] and molecular dynamics simulations of the thermal properties [15] of 2D materials, over numerical simulations and compact modeling of 2D transistors [16][17][18] and other 2D devices [19,20], 2D material growth [21,22] and processing issues [22][23][24], up to experimental 2D devices and their applications [22,23,25]. Regarding the materials, the papers of the Special Issue deal with graphene and graphene nanoribbons [16][17][18][19][20]22,23,25], TMDs (transition metal dichalcogenide) [14,21,22,24,25], phosphorene, which frequently is called 2D black phosphorus [24,25], and 2D metal oxides [25].…”
Section: The Present Special Issuementioning
confidence: 99%
“…Yogeesh and coauthors review their recent progress on flexible graphene devices and demonstrate a flexible graphene-based radio frequency receiver operating at 2.4 GHz [23]. Bablich, Kataria, and Lemme present a thorough overview on the application of 2D materials in optoelectronics [22], and, in the last review paper, Varghese and coauthors comprehensively discuss the use of 2D materials for gas sensors [25].…”
Section: The Present Special Issuementioning
confidence: 99%
“…This Special Issue comprises a total of 12 papers (four review papers and eight contributed articles) and spans a wide range of topics, which extend from first principle band structure calculations [14] and molecular dynamics simulations of the thermal properties [15] of 2D materials, over numerical simulations and compact modeling of 2D transistors [16][17][18] and other 2D devices [19,20], 2D material growth [21,22] and processing issues [22][23][24], up to experimental 2D devices and their applications [22,23,25]. Regarding the materials, the papers of the Special Issue deal with graphene and graphene nanoribbons [16][17][18][19][20]22,23,25], TMDs (transition metal dichalcogenide) [14,21,22,24,25], phosphorene, which frequently is called 2D black phosphorus [24,25], and 2D metal oxides [25].…”
Section: The Present Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the exposure of NH 3 , which act like an electron donor, increases the resistance value whereas electron-withdrawing NO 2 cause a decrease in resistance. 105 An implantable silk-fibroin encapsulated graphene-FET enzymatic biosensor that utilizes silkprotein both as enzyme immobilization material, and a device substrate-was developed for real-time glucose monitoring up to 3-10 mM. 106 Myung et al have reported rGO encapsulated with silicon-oxide NPs based FET biosensor that significantly increases the surfaceto-volume ratio and maintain high electrical conductivity for selective and sensitive real time detection of key biomarker proteins for breast cancer.…”
mentioning
confidence: 99%